Learning vicarious program’s effect in the attitudes to healthy lifestyle in childern from city Huanuco – 2014 - Sánchez Infantas, Rosario Elva (2017)
Our research is applied type - methodological, which seeks to determine what effect a vicariouslearning program in attitudes towards a healthy lifestyle among children of the city of Huánuco. Theexperimental design was employed to verify the hypothesis was: Determine the effect of vicariouslearning program in attitudes towards healthy lifestyle among children of the city of Huánuco. It featured the participation of all students in third grade EI Mario Vargas Llosa Potracancha (35subjects) and with the participation of all students in third grade EI Pitumama (36 subjects) aspopulation, of whom worked with a total of 71 subjects who met the inclusion and exclusion criteria;and they belonged to the I.E. Mario Vargas Llosa Potracancha 35 subjects and 36 belonged to theIE Pitumama. The instruments used were the Guide semi-structured interview on emerging contentthat requires expansion in the available information (authors) and Guide document analysis aboutspecific extract of various relevant documents (authors) content.The main objective was to enable a statistically significant attitudes towards a healthy lifestyleamong children of the city of Huánuco by an increase vicarious learning program.Finding and results are statistically similar groups, so it is considered that there is no differencebetween the control group (IE Pitumama) and experimental group (IE Potracancha).These results allow us to conclude that after the implementation of the program the childrenparticipating in the program mainly found in the middle and upper levels of the variable studied,however it is not possible to state that the results are due to the treatment applied whenever similarresults were found in children who received no treatment. Since the input levels of the variablestudied in both populations were not known, nor is it possible to say that the program has not beeneffective.